2014
DOI: 10.5539/gjhs.v7n4p1
|View full text |Cite
|
Sign up to set email alerts
|

Health Care Utilization and Expenditures in Persons Receiving Social Assistance in 2012 Evidence From Switzerland

Abstract: Introduction:Lower socioeconomic position and measures of social and material deprivation are associated with morbidity and mortality. These inequalities in health among groups of various statuses remain one of the main challenges for public health. The aim of the study was to investigate differences in health care use and costs between recipients of social assistance and non-recipients aged 65 years and younger within the Swiss healthcare system.Methods:We analyzed claims data of 13 492 individuals living in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 20 publications
1
11
0
Order By: Relevance
“…Being male, younger, healthier, and living alone was also found to be associated with higher failure to pay insurance premiums in Switzerland [ 19 ], and could partly support our findings of either delayed healthcare or lack of healthcare needs in groups with these attributes. Reich et al showed that persons of lower socioeconomic status, who receive social assistance, generally have higher intensity and cost of healthcare [ 20 ], which parallels our weak association of no HIC among individuals from high Swiss-SEP regions. Similarly as in the case of mortality, the use of ecological instead of individual SEP may be a reason for weaker association [ 17 ].…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Being male, younger, healthier, and living alone was also found to be associated with higher failure to pay insurance premiums in Switzerland [ 19 ], and could partly support our findings of either delayed healthcare or lack of healthcare needs in groups with these attributes. Reich et al showed that persons of lower socioeconomic status, who receive social assistance, generally have higher intensity and cost of healthcare [ 20 ], which parallels our weak association of no HIC among individuals from high Swiss-SEP regions. Similarly as in the case of mortality, the use of ecological instead of individual SEP may be a reason for weaker association [ 17 ].…”
Section: Discussionsupporting
confidence: 79%
“…Similarly as in the case of mortality, the use of ecological instead of individual SEP may be a reason for weaker association [ 17 ]. The Reich et al study also identified higher rates of social assistance among those suffering from psychological disorders and psychoses (identified using pharmaceutical cost groups) [ 20 ], which supports the idea that these groups might be more economically vulnerable. Mental illness has been associated with problems in paying medical bills [ 21 ] and forgone medical and prescription care [ 22 ], and these findings parallel results of this study.…”
Section: Discussionmentioning
confidence: 80%
“…The disparity in health care expenditure between adult women with and without social welfare was greatest in younger women. The study, unfortunately, did not identify costs related to maternity care . There is growing evidence that health care in high‐income countries has been affected by the economic downturn.…”
Section: Discussionmentioning
confidence: 99%
“…Supplementary hospital insurance in Switzerland is purchased, if individuals wish further comfort of a semiprivate or private ward or treatment in another canton for personal reasons. Currently, there are 57 insurance companies providing basic health coverage in Switzerland., They offer a range of different premiums and types of health plans from which Swiss residents are free to choose among them managed care health plans [ 12 ].…”
Section: Methodsmentioning
confidence: 99%